Unifying Theories of Programming with Monads - Gibbons, J (2012)
The combination of probabilistic and nondeterministic choice in program calculi is a notoriously tricky problem, and one with a long history. We present a simple functional programming approach to this challenge, based on algebraic theories of computational effects. We make use of the powerful abstraction facilities of modern functional languages, to introduce the choice operations as a little embedded domain-specific language rather than having to define a language extension; we rely on referential transparency, to justify straightforward equational reasoning about program behaviour.